2020
DOI: 10.1155/2020/9294605
|View full text |Cite
|
Sign up to set email alerts
|

Zhibaidihuang Decoction Ameliorates Cell Oxidative Stress by Regulating the Keap1‐Nrf2‐ARE Signalling Pathway

Abstract: Zhibaidihuang decoction (ZBDHD) is a Chinese herbal formula, which is used in Chinese traditional medicine to treat symptoms of Yinxuhuowang (Yin deficiency and high fire) syndrome. This study elucidates the mechanism of ZBDHD on oral ulcers, one Yinxuhuowang syndrome. Simultaneously, some ingredients in ZBDHD were found and identified by ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). A Ganjiangfuzirougui decoction- (GJD-) induced Yinxuhuowang syndrome SD rat model was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For example, the study of the protective effect of ZDW on gentamycin-induced renal tubular cell apoptosis in mice suggests ZDW can reduce apoptosis and necrosis [ 8 ]. Another study showed ZDW can improve oral cell inflammation and the imbalance of metabolism by inhibiting NF- κ B and enhancing the activity of the ARE signaling pathway to ameliorate oxidative stress in the cultured cells [ 5 ]. Thus, we suggested the protective effect of ZDW is efficient in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the study of the protective effect of ZDW on gentamycin-induced renal tubular cell apoptosis in mice suggests ZDW can reduce apoptosis and necrosis [ 8 ]. Another study showed ZDW can improve oral cell inflammation and the imbalance of metabolism by inhibiting NF- κ B and enhancing the activity of the ARE signaling pathway to ameliorate oxidative stress in the cultured cells [ 5 ]. Thus, we suggested the protective effect of ZDW is efficient in different experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it was used to treat chronic kidney disease and diabetic nephropathy and to regulate immunity, even was used to treat chronic renal insufficiency and relieve the symptoms [ 1 – 4 ]. The laboratory results showed that ZDW is able to regulate the inflammatory response and heart function and to treat diabetic nephropathy [ 5 , 6 ]. In rats, ZDW treatment could lead to protein alteration in immune response, especially in coagulation and complement cascades [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High dose ZBDHD treatment attenuated AZC induced distractive expression of cytokines, Sirt1, NF-κB, and TNF-α (Figures 3 and 4). e results of our previous study also indicated that AZC can stimulate the expression of NF-κB [13]. e expression of cytokines in Sirt1 signaling pathway was quantitatively analyzed by western blot (Figure 5).…”
Section: Discussionmentioning
confidence: 78%
“…In modern medicine, oral ulcer is a kind of inflammatory diseases, which occurs due to a damage in epithelium induced by many certain factors, such as hormonal changes [23], lack of essential vitamins [24], and Evidence-Based Complementary and Alternative Medicine disorder of metabolism which could induce oral ulcer [25]. It is validated by clinical trial that ZBDHD treatment could promote the ulcer healing [26] and improve the fitness of recurrent oral ulcer significantly [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation